Elevated rates of sister chromatid exchange at chromosome ends. - M Katharine Rudd; Cynthia Friedman; Sean S Parghi; Elena V Linardopoulou; Li Hsu; Barbara J Trask (PLoS Genetics, 2007)
Chromosome ends are known hotspots of meiotic recombination and double-strand breaks. We monitored mitotic sister chromatid exchange (SCE) in telomeres and subtelomeres and found that 17% of all SCE occurs in the terminal 0.1% of the chromosome. Telomeres and subtelomeres are significantly enriched for SCEs, exhibiting rates of SCE per basepair that are at least 1,600 and 160 times greater, respectively, than elsewhere in the genome.